(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
In this article, subsensory speech and unconscious awareness are described as a phenomenon that complements awareness. By the 21st century, the development of effective methods, the creation of scientific research and the formation of directions within the framework of the sciences of philosophy and psychology in the world, which have made a certain contribution to the study of consciousness and unconsciousness, are of great importance. The article deals with the influence of the unconscious ustanovka on the intellectual process, the formation of the ustanovka mechanism at the unconscious level.